The Effects of The Post-2013 Socio-Political Turmoil on International Tourism Demand in Emerging Economies: An Oaxaca-Blinder Decomposition Approach - Erbil, Can; Karaoğlan, Deniz; Yurtseven, Çaglar (Bogazici Universitesi, 2023)
This paper examines the differentiating effects of increasing socio-political risk on international tourism in emerging countries after 2013. In the recent high-risk period, the world faces not only financial but also socio-political challenges. The study demonstrates the effects of specific socio-political based uncertainty on tourism demand by using Oaxaca-Blinder decomposition analysis. This method provides the premise place of this study in the literature. The findings suggest that the increase in socio-political uncertainty in the post-2013 period acts as a decelerator in the number of tourist arrivals in emerging countries between 2013 and 2017. Therefore, although the incentives in the global market dramatically expand in the post-2013 period, the increasing socio-politic uncertainty world-wide has a large-scale negative impact on tourism demand in emerging countries. © 2023 Elsevier B.V., All rights reserved.
2013 Sonrası Sosyo-Politik Kargaşanın Uluslararası Turizm Talebi Üzerindeki Gelişmekte Olan Ekonomilere Etkileri: Bir Oaxaca-Blinder Ayrışma Yaklaşımı
Keywords: Emerging countries; Oaxaca-Blinder decomposition; sociopolitical issues; tourism; tourism demand; uncertainty